1987
DOI: 10.1021/bk-1988-0361.ch010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Analytical Calibration Models on Detection Limit Estimates

Abstract: Detection limit estimates derived from confidence bands around analytical calibration curves are highly dependent on the experimental design and on the statistical data treatment. Procedures are described for testing the linearity of data and whether the intercept differs significantly from zero. Insensitivity of the correlation coefficient for the evaluation of goodness of fit of calibration models is emphasized, unweighted linear models with an intercept often yield overly conservative detection limits. Freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The unweighted intervals are wider than the weighted intervals at very low concentration and provide a poor fit to the actual data (see Figure ). As a result, applying unweighted least-squares regression in situations of nonconstant variance generally yields overestimated detection limits. ,, Table lists the unweighted detection limit for all 16 PCB congeners. Unweighted values range from 3 times the weighted value (tolerance interval-based detection limit for PCB congener 128) to nearly 60 times the weighted value (prediction interval-based detection limit for PCB congener 18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unweighted intervals are wider than the weighted intervals at very low concentration and provide a poor fit to the actual data (see Figure ). As a result, applying unweighted least-squares regression in situations of nonconstant variance generally yields overestimated detection limits. ,, Table lists the unweighted detection limit for all 16 PCB congeners. Unweighted values range from 3 times the weighted value (tolerance interval-based detection limit for PCB congener 128) to nearly 60 times the weighted value (prediction interval-based detection limit for PCB congener 18).…”
Section: Resultsmentioning
confidence: 99%
“…Also, if the response values are transformed, linearity of the calibration curve will likely be compromised, and an appropriate transformation for the X axis will be required in order to retain linearity. This can be problematic, and, as several previous authors have pointed out, ,, a better solution is to use weighted least-squares regression.…”
mentioning
confidence: 99%
“…Often, the errors do not exhibit constant variance; nonconstant variance has been previously documented for various chemical analyses and analytes ( ). Several authors ( 5 , 11 , 13 , 14 ) have suggested using weighted least-squares (WLS) regression for calculating limits of detection and quantification in situations of nonconstant variance.…”
Section: Introductionmentioning
confidence: 99%